The effects of different infectious organisms on platelet counts and platelet indices in neonates with sepsis: Is there an organism-specific response? - Akarsu, S; Taskin, E; Kilic, M; Ozdiller, S; Gurgoze, MK; Yilmaz, E; Aygun, AD (Oxford Univ Press, 2005)
[Abstract Not Available]
Keywords: Intensive-Care-Unit; Thrombocytopenia; Infants; Volume